2003
DOI: 10.1001/archinte.163.21.2625
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Decisions to Override Computerized Drug Alerts in Primary Care

Abstract: Few physicians changed their prescription in response to a drug allergy or interaction alert, and there were few ADEs, suggesting that the threshold for alerting was set too low. Computerized physician order entry systems should suppress alerts for renewals of medication combinations that patients currently tolerate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
342
4
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 433 publications
(371 citation statements)
references
References 14 publications
20
342
4
5
Order By: Relevance
“…5 Several alternative suggestions to reduce alert overload were made by our study prescribers. Similar to previous reports, 14 prescribers in our study suggested suppressing alerts for renewals of medication combinations that patients currently tolerate. Providers in our study often noted that short-term courses of therapy would continue to arise in the alerts, suggesting that the time frame for medication history on which the drug alerts are run should be evaluated.…”
Section: Discussionsupporting
confidence: 90%
“…5 Several alternative suggestions to reduce alert overload were made by our study prescribers. Similar to previous reports, 14 prescribers in our study suggested suppressing alerts for renewals of medication combinations that patients currently tolerate. Providers in our study often noted that short-term courses of therapy would continue to arise in the alerts, suggesting that the time frame for medication history on which the drug alerts are run should be evaluated.…”
Section: Discussionsupporting
confidence: 90%
“…Studies may be conducted in silico, in vitro or in vivo, the latter comprising formal pharmacokinetic interaction studies in animals and humans, or as reports of clinical observations.The assessment of these studies is seldom explicit, and there is lack of consistency and considerable disparity between resources [2][3][4][5][6]. For example, in a recent study of four international drug interaction compendia, between 14% and 44% of the interactions classified as major in any one compendium were not listed in other compendia [4].Thus, interpreting the clinical relevance of a given perpetrator is often difficult, particularly for healthcare providers subject to 'information overload' and 'alert fatigue' [7,8]. Computerized DDI checkers at the point of prescribing appear no better, delivering alerts that are frequently irrelevant to clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Decision Support Systems have been widely implemented and adopted in commercial fields 52 ; however their acceptance within the medical domain remains limited 53,54,55,56 . This review aimed to provide clinicians and policy makers with a better understanding of the methodologies CDSSs employ as the development and deployment of systems that can meaningful support clinicians in practice requires their collaboration.…”
Section: Discussionmentioning
confidence: 99%